Meningkatkan Kemampuan Penjumlahan Bilangan Melalui Media Counting Box Pada Anak Disabilitas Intelektual Ringan - Marisa, Agus; Damri, Damri; Tsaputra, Antoni; Arnez, Gaby (Lembaga Riset dan Inovasi Almatani, 2026)
This study was based on the low ability of second-grade students with mild intellectual disabilities at SLBN 02 Pariaman in adding numbers 1 to 10, which resulted in limitations in their daily activities. This study aims to improve addition skills through the use of box counting media. The method used is Single Subject Research (SSR) with an A-B design. The subject of the study was a child with mild intellectual disabilities. Data collection techniques were carried out through observation and testing, while data analysis used a visual analysis approach by comparing data between conditions and within conditions. The results of the study showed a significant increase in addition skills after intervention using box counting media, as evidenced by an increase in scores in the intervention phase compared to the baseline phase. In the baseline phase (A), which was carried out for 4 sessions, the results achieved were 0%. Furthermore, in the intervention phase (B), which was carried out for 8 sessions, the results increased gradually from 45%, 50%, 55%, 65%, 85% to reach 100% for the final 3 meetings. Thus, counting cubes has been shown to improve children with mild intellectual disabilities' addition skills from 1 to 10. Therefore, this tool can be recommended as an alternative mathematics learning tool for children with special needs and elementary school students.